Respon Pertumbuhan Tunas Lidah Buaya (Aloe barbadensis Mill.) Dengan Penambahan Ekstrak Taoge dan BAP (Benzyl Amino Purine) - Riza Linda, Serafina Rita, Mukarlina, (Universitas Tanjungpura, 2017)
Aloe vera (Aloe barbadensis Mill.) can be regenerated using in vitro to get identical plants as their mother plants by adding bean sprout extract and BAP. This research work aimed to investigate the effect of bean sprout extract and BAP on growth of Aloe vera’s roots. This research was conducted from December 2016 to January 2017 at tissue culture laboratory of Aloe centre Pontianak. The treatments were arranged in a completely randomized design with two treatments. The firs factor, bean sprout extract (0%, 12,5%, 15%) and the second factor BAP (0 M, 10-6 M, 10-7M) were apllicated. The bean sprout extract and BAP treatment and their interaction enhanced growth of shoots, leaves, and roots contents. Concentration of 12,5% of bean sprout + 10-7 of BAP was 1,67 shoot, concentration of 12,5% of bean sprout + 10-7 of BAP was 2,67 leavesand concentration of 12,5% of bean sprout + 10-7 of BAP was 2 roots.